Forging African Communities Mobility, Integration and Belonging (Global Diversities,, 2018)
This book draws renewed attention to migration into and within Africa, and to the socio-political consequences of these movements. In doing so, it complements vibrant scholarly and political discussions of migrant integration globally with innovative, interdisciplinary perspectives focused on migration within Africa. It sheds new light on how human mobility redefines the meaning of home, community, citizenship and belonging. The authors ask how people's movements within the continent are forging novel forms of membership while catalysing social change within the communities and countries to which they move and which they have left behind. Original case studies from across Africa question the concepts, actors, and social trajectories dominant in the contemporary literature. Moreover, it speaks to and challenges sociological debates over the nature of migrant integration, debates largely shaped by research in the world's wealthy regions. The text, in part or as a whole, will appeal to students and scholars of migration, development, urban and rural transformation, African studies and displacement.